Life in the slow lane; biogeochemistry of biodegraded petroleum containing reservoirs and implications for energy recovery and carbon management - Head, Ian M.; Gray, Neil D.; Larter, Stephen R. (Frontiers in Microbiology, 2014)
Our understanding of the processes underlying the formation of heavy oil has been transformed in the last decade. The process was once thought to be driven by oxygen delivered to deep petroleum reservoirs by meteoric water. This paradigm has been replaced by a view that the process is anaerobic and frequently associated with methanogenic hydrocarbon degradation. The thermal history of a reservoir exerts a fundamental control on the occurrence of biodegraded petroleum and microbial activity is focussed at the base of the oil column in the oil water transition zone that represents a hotspot in the petroleum reservoir biome. Here we present a synthesis of new microbiological, geochemical and biogeochemical data that expands our view of the processes that regulate deep life in petroleum reservoir ecosystems and highlights interactions of a range of biotic and abiotic factors that determine whether petroleum is likely to be biodegraded in situ, with important consequences for oil exploration and production. We also discuss the role of microbial processes for energy recovery in the future and how this fits within the broader socioeconomic landscape of energy futures.